2010
DOI: 10.1590/s0074-02762010000600018
|View full text |Cite
|
Sign up to set email alerts
|

Differential tissue tropism of Trypanosoma cruzi strains: an in vitro study

Abstract: We have previously demonstrated selection favoring the JG strain of Trypanosoma cruziin hearts of BALB/c mice that were chronically infected with an equal mixture of the monoclonal JG strain and a clone of the Colombian strain, Col1.7G2. To evaluate whether cell invasion efficiency drives this selection, we infected primary cultures of BALB/c cardiomyocytes using these same T. cruzi populations. Contrary to expectation, Col1.7G2 parasites invaded heart cell cultures in higher numbers than JG parasites; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 21 publications
4
35
2
11
Order By: Relevance
“…This selection was due to higher intracellular multiplication of the JG strain (26). Another study conducted using a mixture of Tc I and Tc II strains in murine and human macrophages also showed that Tc II strains have a higher proliferative ability, as well as lower doubling time inside macrophages, as compared to Tc I (27).…”
Section: Chagas Disease: a Complex Host-parasite Interaction Drives Pmentioning
confidence: 99%
“…This selection was due to higher intracellular multiplication of the JG strain (26). Another study conducted using a mixture of Tc I and Tc II strains in murine and human macrophages also showed that Tc II strains have a higher proliferative ability, as well as lower doubling time inside macrophages, as compared to Tc I (27).…”
Section: Chagas Disease: a Complex Host-parasite Interaction Drives Pmentioning
confidence: 99%
“…Although infective T. cruzi trypomastigotes are capable of invading a wide variety of tissues and cell types in the vertebrate host, the majority of T.cruzi laboratory strains and isolates have tropism for cardiac tissue and or cardiomyocytes [32] . The establishment of a long-term infection in the heart and the development of a cardiomyopathy condition are directly related to the ability of T. cruzi to infect and persist within cardiomyocytes during the acute phase of infection [33,34] .…”
Section: Tcruzimentioning
confidence: 99%
“…Patients infected with T. cruzi I demonstrated a higher prevalence of cardiac alterations than those infected with T. cruzi II (Ramírez et al, 2010). These two DTUs behave differently with respect to their virulence, capacity for cell invasion, infectiveness (reviewed by Mortara et al, 2005;Andrade et al, 2010), capacity for vector transmission (Lana et al, 1998), and resistance to chemotherapeutic agents .…”
Section: Introductionmentioning
confidence: 99%